Synthesis of Novel Chalcone Substituted Metallophthalocyanines: Electrochemistry, Spectroelectrochemistry, and Catalytic Oxidation of 2-mercaptoethanol - (:unkn) unknown (My University, 2018)
Novel metallophthalocyanines (M = Zn, Co) carrying four (E)-1-(furan-2-yl)-3-(4-hydroxyphenyl)prop-2-en-1-one (chalcone) at the peripheral positions were sythesized. Thesecomplexes have been characterized by a combination of infrared spectroscopy (FT-IR), protonNMR (1H-NMR), high resolution mass spectroscopy (HRMS), and ultraviolet visible (UV–Vis)spectrophotometry techniques. Also, cyclic voltammograms of these phthalocyanines wererecorded and zinc phthalocyanine has one and cobalt phthalocyanine has two reductionreactions. Spectroelectrochemical investigation shows the ring-based reduction of MPcs. Pc-7cobalt(II) phthalocyanine was investigated as a catalyst in the catalytic oxidation of 2-mercaptoethanol. Turnover number, initial reaction rate, and the oxygen consumption werefound in the catalytic oxidation of 2-mercaptoethanol as 16.6, 0.29, 2.52, respectively.
Keywords: Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Fizikokimya; Spektroskopi; Termodinamik